Sodium Accumulation and Blood Capillary Rarefaction in the Skin Predispose Spontaneously Hypertensive Rats to Salt Sensitive Hypertension - Šilhavý, Jan; Mlejnek, Petr; Šimáková, Miroslava; Liška, František; Kubovčiak, Jan; Sticová, Eva; Pravenec, Michal (Biomedicines, 2022)
Recent studies in humans and rats suggested that increased Na+ storage in the skin without parallel water retention may predispose to salt-sensitive hypertension. In the current studies, we compared tissue Na+ storage in salt sensitive spontaneously hypertensive rats (SHR) versus salt resistant normotensive Brown Norway (BN-Lx) rats. After salt loading (10 days drinking 1% NaCl solution), the SHR showed significant parallel increase in Na+-to-water as well as (Na++K+)-to-water ratios suggesting increased storage of osmotically inactive Na+ in the skin while no significant changes in skin electrolyte concentrations were observed in BN-Lx rats. SHR rats after salt treatment exhibited a nonsignificant decrease in skin blood capillary number (rarefaction) while BN-Lx rats showed significantly increased skin blood capillary density. Analysis of dermal gene expression profiles in BN-Lx rats after salt treatment showed significant up-regulation of genes involved in angiogenesis and proliferation of endothelial cells contrary to the SHR. Since the skin harbors most of the body's resistance vessels it is possible that blood capillary rarefaction may lead to increased peripheral resistance and salt sensitivity in the SHR.
Keywords: capillary rarefaction; spontaneously hypertensive rat; salt; salt-sensitive hypertension; blood pressure; sodium; skin; gene expression